MEMAJUKAN SDGs MELALUI PEKERJAAN PERHOTELAN INKLUSIF: PERUSAHAAN BERBASIS KOMUNITAS DI BALI - Pertiwi, Putu Ratih; Pratama, I Putu Andre Adi Putra; Indrawati, Yayu; Dewi, Luh Gede Leli Kusuma (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
This study examined how inclusive hospitality employment was enacted and experienced within a local community-based enterprise in Bali and how such practices contributed to advancing the Sustainable Development Goals, particularly SDG 8 on Decent Work and Economic Growth and SDG 10 on Reduced Inequalities. Grounded in an interpretivist qualitative approach, the research was conducted at Piduh Café, a locally embedded hospitality enterprise employing persons with disabilities. Data were generated through participatory observation, informal in-depth interviews with nine employees with disabilities and two organisational informants, and documentation review. The findings showed that inclusive employment extended beyond technical skill acquisition to encompass the development of work identity, self-confidence, social interaction, and economic participation. Meaningful job matching, experiential learning, adaptive supervision, and fair remuneration enabled employees to perceive themselves as capable workers and valued contributors. At the organisational and community levels, inclusive employment fostered workplace cohesion, household economic support, and gradual shifts in local attitudes toward disability. The study concluded that inclusive hospitality employment functioned as a relational and context-specific process through which global development agendas were locally interpreted and embedded in everyday practice. Rather than scale, the depth and consistency of inclusive practices emerged as the key contribution of community-based enterprises to sustainable and inclusive tourism development